The Influence of Role Perception, Human Resource Development, and Compensation on Employee Performance Universitas Ibnu Sina - Zhalfa Putri Elisa; Septa Diana Nabella; Sabri; Dewi Permata Sari; Nurmayunita (Institute of Computer Science (IOCS), 2022)
Employee performance improvement is based on the willingness to mobilize all elements of human resources. This study aims to determine the effect of role perception, human resource development, and compensation on employee performance. This type of research is causality with a quantitative approach. The study has a population of 109 employees of Ibn Sina University. The number of samples obtained by the slovin formula amounted to 85 respondents. The sampling method used is Simple Random Sampling. The data analysis approach used is multiple linear regression. The result of this research is that there is a positive influence of role perception, human resource development, and compensation partially and simultaneously on employee performance. This study provides findings that there is an empirical model development on employee performance that is influenced by role perceptions, human resource development, and compensation.